The Effect of Problem Based Learning Model on Students' Critical Thinking Ability - Awaliyah, Nur Putri; Hastuti, Woro Sri; Wibowo, Setiawan Edi; Hidayat, Panji (Universitas Pendidikan Ganesha, 2024)
Students still experience difficulties developing critical abilities, so students still experience difficulties working in groups, communicating, solving problems, and making decisions as the right solution to a problem. This study aimed to analyze whether the problem-based learning (PBL) learning model, through science learning, affected students' critical thinking skills. This study used a quasi-experimental design with a pretest-posttest control design. Methods of data collection using observation and documentation methods using research instruments. The data analysis technique used is quantitative descriptive analysis. The sample of this research is 25 students. Based on the hypothesis testing obtained through the t-test calculation with a significant level (a) 0.05 and dk = 25-2 = 23, the value of tcount = 27.98 is obtained. Thus, it can be concluded that t-count > t-table or 27.98 > 2.069, then H0 is rejected and Ha is accepted, meaning that the hypothesis stating that the problem-based learning method influences the critical thinking skills of class 4H students at Ahmad Dahlan University is accepted as true. It was concluded that the problem-based learning method influenced the critical thinking skills of class 4H students.